1997
DOI: 10.1046/j.1365-2249.1997.d01-905.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased IL-6 and IL-8 in bronchoalveolar lavage fluids (BALF) from patients with sarcoidosis: correlation with the clinical parameters

Abstract: SUMMARYA variety of cytokines have been implicated in the pathogenesis of pulmonary sarcoidosis, but the exact roles of IL-6 and IL-8 are not yet clear. We studied these cytokine levels in BALF from patients with pulmonary sarcoidosis, idiopathic pulmonary fibrosis (IPF), systemic screlosis (SSc) with interstitial lung disease and control subjects. IL-6 and IL-8 levels were significantly elevated in sarcoidosis, IPF and SSc with interstitial lung disease compared with control subjects. Subjects with sarcoidosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
44
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(48 citation statements)
references
References 16 publications
3
44
1
Order By: Relevance
“…29 We and others have found that IL6 levels are elevated in the bronchoalveolar lavage (BAL) and serum obtained from sarcoidosis patients. [30][31][32] After D5S2500, the next most significant result was with D5S211 on 5q35.2 (P ¼ 0.005). Two patients with 5q myelodysplasia and sarcoidosis have been reported, 33,34 suggesting that a chromosome 5q abnormality may predispose to sarcoidosis through loss of genes coding Figure 3 Chromosome 3, 6, 9 and 13 genome scan results for sarcoidosis susceptibility in African-American nuclear families ascertained through two affected sibs.…”
Section: Discussionmentioning
confidence: 99%
“…29 We and others have found that IL6 levels are elevated in the bronchoalveolar lavage (BAL) and serum obtained from sarcoidosis patients. [30][31][32] After D5S2500, the next most significant result was with D5S211 on 5q35.2 (P ¼ 0.005). Two patients with 5q myelodysplasia and sarcoidosis have been reported, 33,34 suggesting that a chromosome 5q abnormality may predispose to sarcoidosis through loss of genes coding Figure 3 Chromosome 3, 6, 9 and 13 genome scan results for sarcoidosis susceptibility in African-American nuclear families ascertained through two affected sibs.…”
Section: Discussionmentioning
confidence: 99%
“…123 As the lung is a common site of involvement in this disease, the phenotypic profile of T cells from bronchoalveolar lavage has shown an increased CD4 + /CD8 + ratio, which may aid in its diagnosis. 124 Raised bronchoalveolar lavage levels of IFN-γ, TNF-α, 125 IL-12, 126 IL-6 and IL-8 127 have all been detected, while only a few cells positive for IL-4 have been observed, suggesting a polarization towards a Th1 cytokine profile. 125 With successful corticosteroid treatment, the balance between Th1 and Th2 has been restored.…”
Section: Behçet's Diseasementioning
confidence: 99%
“…In order to understand this supposed mechanism in sarcoidosis, we therefore focused our work on critical cell surface receptors which bind exogenous stimuli [2][3][4]. It is well established that immunity-related receptors and proinflammatory cytokines, which include tumour necrosis factor (TNF)-α [5], interleukin (IL)-1 β [6], IL-2 [7], IL-6, IL-8 [8] and interferon (IFN)-γ [9], play a pivotal role in the formation of granulomas in sarcoidosis. The early phase in developing sarcoid granulomas is characterized by the accumulation and activation of T helper cells type 1 (Th1) lymphocytes, which lead to an immune response.…”
Section: Introductionmentioning
confidence: 99%